A New Approach for the Green Biosynthesis of Silver Oxide Nanoparticles Ag2O, Characterization and Catalytic Application - Brahim El-Ghmari; Hanane Farah; Abdellah Ech-Chahad (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
In this paper, a facile and green approach for the synthesis of silver oxide nanoparticles Ag2O NPs was performed using the extract of the wild plant Herniaria hirsuta (H. hirsuta). Different spectral methods were used for the characterization of the biosynthesized Ag2O NPs, ultraviolet-visible (UV-Vis) spectroscopy gave a surface plasmon resonance (SPR) peak of Ag2O NPs is 430 nm, estimation of direct and indirect forbidden gap bands are respectively 3.76 eV and 3.68 eV; Fourier transform infrared (FTIR) spectral analysis revealed the groups responsible for the stability and synthesis of Ag2O NPs. The morphology of Ag2O NPs was studied by scanning electron microscopy (SEM) showing a nearly spherical shape of Ag2O NPs, and X-ray diffraction (XRD) study confirmed the crystallinity of Ag2O NPs with a crystallinity size of 15.51 nm. The catalytic activity of Ag2O NPs, as well as the rings number were studied by the degradation of methylene blue dye. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).